La crisis de autoridad en el mundo educativo. Una interpretación sociológica - Durán Vázquez, José Francisco (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The present article has as aim analyze the crisis of authority that today concerns the educational world. We pose the hypothesis of which this crisis is related to the changes happened in areas so changed as those of the family, the work, the consumption, the State, and the own school area. It thinks, in addition, that these changes it is necessary to place them in a historical perspective, attending to the process of conformation of the modern societys. In effect, if in the first stage, that of the first modernity, the authority had been sustained by the disciplinary order created by the institutions before mentioned; in the second modernity, the above mentioned order would have lost his previous legitimacy, emerging a subjectivity without obstacles, of which also youngs and childrens take part. The exercise of the authority remained like that without institutional links on which to rest. Nevertheless, the absence of authority coexists with the putting in practice of a domination increasingly individualistic and therapeutic, whose intention, paradoxically, is to liberate to the subjects.
Keywords: Authority; education; crisis; Modernity